(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Nutrient supplies from internal sources of soil can be estimated by measuring plant nutrient uptake in nutrient omission plots. On farm experiments were conducted in rice (Oryza sativa L.) domains of Chhattisgarh state of India to develop guidelines for the use of omission plots in site specific nutrient management. In these experiments, significant site variations were observed in respect of soil test values, grain yields in nutrient omitted and applied plots, nutrient uptake and its efficiency of utilization. However, grain yields correlated significantly with nutrients (N, P, and K) uptake in nutrient omitted and applied plots, but it showed positive correlation only with soil test N in nutrient omitted plots. Similarly, relationship of nutrients uptake with soil test values gave significantly high R2 values for nitrogen and phosphorus in nutrient omission plots indicating lower internal N & P supply (INS &IPS) and significantly higher K supply capacity (IKS) of soils (Vertisols). INS, IPS, and IKS varied from 21.24 to 37.39, 7.50 to 12.22, and 93.99 to 115.86 kg/ha, respectively. Farmers’ fertilizer practice gave significantly lower yield than with recommended fertilizer practices at majority of sites with yield difference of more than 10 q/ha. Bangladesh J. Agril. Res. 32(4) : 501-507